(untitled) (The International Journal for Scientific Research, 2023)
This study seeks to reveal the idea of ​​the savior man and the victory of good over evil. It is one of the beliefs that man believed in since ancient times. In addition to the monotheistic religions that emphasized it, the positive religions also called for it and surrounded it with an aura of sanctity, as it is one of the basic points of commonality between most religions. This is because the issue of salvation preoccupied the mind of man, and he kept looking for a savior, whether this savior was embodied in a god or a human being. Thus, this belief is not exclusive to the divine religions only, as it stems mainly from the human instinct that constantly longs for perfection in all its forms, and perhaps this matter in particular. It is what makes it more realistic. Human nature, as is well known, does not seek something that does not exist. Therefore, all religions, including man-made religions, preached that humanity has a promised day when the earth will be honored with the appearance of the savior and the savior. No ideology, whatever its stance on the unseen, can deny the idea of ​​salvation, for all of them meet in terms of the content of faith in waiting for a savior or savior who will rid humanity of injustice and persecution, and lead it to terms of freedom, justice and prosperity, even if the reasons for this belief differ.